2013
DOI: 10.4306/pi.2013.10.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Attributional Style in Healthy Persons: Its Association with 'Theory of Mind' Skills

Abstract: ObjectiveAttributional style, especially external personal attribution bias, was found to play a pivotal role in clinical and non-clinical paranoia. The study of the relationship of the tendency to infer/perceive hostility and blame with theory of mind skills has significant theoretical importance as it may provide additional information on how persons process social situations. The aim of this study was whether hostility perception bias and blame bias might be associated with theory of mind skills, neurocogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…The results showed that the cardiac integrated intervention program significantly improved the quality of life, and reduced the type D personality in the intervention group. The results are consistant with the findings of previous studies (31)(32)(33)(34)(35) that confirmed the significant effect of psychological interventions in decreasing the psychosocial risk factors among cardiac patients. This program focuses on irrational beliefs, emotion regulation styles, behavioral coping strategies, and the context, which the patient lives and works in it.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that the cardiac integrated intervention program significantly improved the quality of life, and reduced the type D personality in the intervention group. The results are consistant with the findings of previous studies (31)(32)(33)(34)(35) that confirmed the significant effect of psychological interventions in decreasing the psychosocial risk factors among cardiac patients. This program focuses on irrational beliefs, emotion regulation styles, behavioral coping strategies, and the context, which the patient lives and works in it.…”
Section: Discussionsupporting
confidence: 89%
“…As other researchers showed, stable, overall and internal attribution styles of negative events lead to mood disorders (34). patients who have rational attribution Styles have a tendency to attribute positive happenings to unchangeable, general, and intrinsic reasons (35). Therefore, developing the unstable, specific, and external attribution style of negative events was one of the main task of participants.…”
Section: Discussionmentioning
confidence: 98%
“…The AIHQ has seen wider dissemination than the PPDFQ. In a predominantly non-psychotic sample of online Korean job-seekers, hostile attribution, as measured by the AIHQ, is related to deficiencies in theory of mind [54]. …”
Section: Dimensionsmentioning
confidence: 99%
“…Lower perspective taking ability in a role playing task has been found to predict the development of Cluster A personality disorders and delusional disorder [93]. Poor theory of mind skills are related to traits of hostility [54]. In an experimental study, the presence of theory of mind deficits was predictive of paranoid attribution [94].…”
Section: Theoretical Models Of Ppdmentioning
confidence: 99%
“…In the case of blame, as a sub-category of attribution style, Jeon et al [52] assessed 263 non-disabled people with an average age of 21.1 years, and reported average scores for motive, anger, and blame of 1.56 ± 0.46, 2.43 ± 0.58, and 1.76 ± 0.28, respectively. Lee [30] assessed people with schizophrenia with an average age of 39.6 years, who participated in vocational rehabilitation through supported employment, and reported motive, anger, and blame scores of 2.53 ± 1.03, 4.15 ± 1.52, and 2.29 ± 0.78, respectively.…”
Section: Discussionmentioning
confidence: 99%